Fatty liver associated with metabolic derangement in patients with chronic kidney disease: A controlled attenuation parameter study - Chang-Yun Yoon; Misol Lee; Seung Up Kim; Hyunsun Lim; Tae Ik Chang; Youn Kyung Kee; Seung Gyu Han; In Mee Han; Young Eun Kwon; Kyoung Sook Park; Mi Jung Lee; Jung Tak Park; et al. (The Korean Society of Nephrology, 2017)
Background: Hepatic steatosis measured with controlled attenuation parameter (CAP) using transient elastography predicts metabolic syndrome in the general population. We investigated whether CAP predicted metabolic syndrome in chronic kidney disease patients. Methods: CAP was measured with transient elastography in 465 predialysis chronic kidney disease patients (mean age, 57.5 years). Results: The median CAP value was 239 (202-274) dB/m. In 195 (41.9%) patients with metabolic syndrome, diabetes mellitus was more prevalent (105 [53.8%] vs. 71 [26.3%], P < 0.001), with significantly increased urine albumin-to-creatinine ratio (184 [38-706] vs. 56 [16-408] mg/g Cr, P = 0.003), high sensitivity C-reactive protein levels (5.4 [1.4-28.2] vs. 1.7 [0.6-9.9] mg/L, P < 0.001), and CAP (248 [210-302] vs. 226 [196-259] dB/m, P < 0.001). In multiple linear regression analysis, CAP was independently related to body mass index (β = 0.742, P < 0.001), triglyceride levels (β = 2.034, P < 0.001), estimated glomerular filtration rate (β = 0.316, P = 0.001), serum albumin (β = 1.386, P < 0.001), alanine aminotransferase (β = 0.064, P = 0.029), and total bilirubin (β = −0.881, P = 0.009). In multiple logistic regression analysis, increased CAP was independently associated with increased metabolic syndrome risk (per 10 dB/m increase; odds ratio, 1.093; 95% confidence interval, 1.009-1.183; P = 0.029) even after adjusting for multiple confounding factors. Conclusion: Increased CAP measured with transient elastography significantly correlated with and could predict increased metabolic syndrome risk in chronic kidney disease patients.